Anisotropic Self-Defocusing in Knbo3: Fe Crystal. (October 2019) - He, Zhenni; Zhang, Xiaohua; Zhang, Chunping
Abstract: All the characteristics of the self-defocusing and "position dispersion" in KNbO3:Fe crystal are experimentally investigated. The results show that the scattering from KNbO3:Fe crystal is mainly due to the photo-induced lensing.